Nexus of Working Capital Management and Firm Performance in Nigerian Food and Beverages Industries: A Link with Risk-Return Theory - Olarewaju, Odunayo Magret; Doorasamy, Mishelle; Oladejo, Titilayo Moromoke (Journal of Economics and Behavioral Studies, 2017)
This paper examines the nexus of working capital management and financial performance of selected multinational food and beverages industries in Nigeria for the period between 2006 and 2014 and establishes its linkage with risk-return theory. An explanatory research design is adopted and the secondary data used were gathered from 5 purposively selected quoted food and beverages companies using GLS panel regression analysis. The pooled regression shows that account receivable ratio (ARR) and debt ratio (DER) have negative effect but significant at 1%, working capital (WCA) is also significant at 5% but had positive effect, however, sales growth (SGR) was insignificant. It is also discovered from the Fixed Effect Estimation that working capital management variables such as account receivable ratio (ARR) and debt ratio (DER) have negative effect but significant at 1%, working capital (WCA) is also significant at 5% but has positive effect, while sales growth (SGR) has negative effect but insignificant to the performance of the companies. This signifies reduction in the performances of food and beverages industries which calls for urgent attention since they are posting inverse effect. The unison in both estimations shows that those variables are the major factors influencing the performance of food and beverages industries in Nigeria and thus, it is concluded that the management board of these industries should restructure their working capital management policy as it has the tendency of affecting the dividend policy and firms’ liquidity, which invariably affects the maximization of shareholders’ wealth. This can only be done when managers reduce account receivable days; ensure proper debt management technique, improve sales strategies to enhance sales growth as well as maintain optimal working capital level to reflect the risk-return theory of firms.